Vocabulary Size Is a Key Factor in Predicting Second Language Lexical Encoding Accuracy - Daidone, Danielle; Darcy, Isabelle (Frontiers in Psychology, 2021)
This study investigates the relationship between the accuracy of second language lexical representations and perception, phonological short-term memory, inhibitory control, attention control, and second language vocabulary size. English-speaking learners of Spanish were tested on their lexical encoding of the Spanish /ɾ-r/, /ɾ-d/, /r-d/, and /f-p/ contrasts through a lexical decision task. Perception ability was measured with an oddity task, phonological short-term memory with a serial non-word recognition task, attention control with a flanker task, inhibitory control with a retrieval-induced inhibition task, and vocabulary size with the X_Lex vocabulary test. Results revealed that differences in perception performance, inhibitory control, and attention control were not related to differences in lexical encoding accuracy. Phonological short-term memory was a significant factor, but only for the /r-ɾ/ contrast. This suggests that when representations contain sounds that are differentiated along a dimension not used in the native language, learners with higher phonological short-term memory have an advantage because they are better able to hold the relevant phonetic details in memory long enough to be transferred to long-term representations. Second language vocabulary size predicted lexical encoding across three of the four contrasts, such that a larger vocabulary predicted greater accuracy. This is likely because the acquisition of more phonologically similar words forces learners’ phonological systems to create more detailed representations in order for such words to be differentiated. Overall, this study suggests that vocabulary size in the second language is the most important factor in the accuracy of lexical representations.